The End of Bureaucracy? New Organizational Forms, Social Media, and Millennials - Asaturyan, Daria (Journal of Economic Sociology, 2021)
In recent years, Silicon Valley startups have become some of the most successful corporations in the world. They advance the abandonment of bureaucratic control of employees, for example, they do not keep track of what time employees come to work or what they are wearing, and instead delegate decision-making rights to employees and are attentive to their opinions. But what happens behind the closed doors of those companies promoting such openness and the overthrow of the hierarchy and bureaucratic rules? How and by whom are they controlled? The book by Catherine J. Turco (2016) shows how corporate communication, culture, and control actually work in a company run by millennials reared on social media. During her ethnographic research, Turco describes how a new organizational form she calls a “conversational firm” has arisen and succeeded in solving business problems due to cross-hierarchical communication. One of Turko’s main findings is that subverting the hierarchical control of communication does not mean the hierarchical structure of decision making must fall as well. Thus, employees may prefer some bureaucratic practices and insist on them.